Systematic Literature Mapping of User Story Research - Anis R. Amna; Geert Poels (IEEE Access, 2022)
User stories are a widely used artifact in Agile software development. Currently, only a limited number of secondary studies have reviewed the research on the user story technique. These research reviews focused on specific research topics related to ambiguity of requirements, effort estimation, and the application of Natural Language Processing. To our knowledge, a systematic mapping of all user story research has not been performed. To this end, we study the academic literature to investigate what user stories research has been performed, what types of problems have been identified, what sort of solutions or other types of research outcomes have been achieved, how mature the research is, and what research gaps exist. We followed Systematic Mapping Study guidelines to synthesize the currently available academic research on user stories. In total, we found 186 unique peer-reviewed studies, published in the period 2001-2021. We observed that research on the user story technique and its use had grown exponentially over the last seven years. Further, using a five-dimensional classification framework– requirements engineering activity, problem class, outcome class, type of research, type of publication– we observed several patterns in the classification of these studies across the different framework dimensions, which provided insights into the state-of-the-art and maturity of the research. We also identified four research gaps: the paucity of focused literature reviews; a lack of research on the role that user stories play in human cognition and interaction; a lack of comprehensive and mature solutions for resolving ambiguity issues with user stories early in the project; and a lack of validation and evaluation of proposed solutions. Several research opportunities are suggested, making our paper a useful reference for future research on user stories allowing researchers to clearly position their contributions.